Attitude of Farmers Toward Intercropping in Haryana - Boora, Sahil; Kaur, Bas; Tyagi, Rashmi; Manisha,; Rohit, (Indian Journal of Extension Education, 2022)
Intercropping is a type of multiple cropping practices that involves the cultivation of two or more crops in definite proximity. The present study was conducted in dry and wet agro-climatic zones of Haryana in March, 2022. Bhiwani and Hisar districts were selected randomly from dry zone and Karnal and Kaithal districts were selected randomly from wet zone with an objective to assess the attitude of farmers toward intercropping. The data were collected personally from 120 respondents comprising 30 from each district through a structured interview schedule. Findings revealed that more than three-fifths of the respondents (50.83%) had a more favourable attitude towards intercropping system whereas 36.67 per cent had a favourable attitude and 12.50 per cent had a less favourable attitude towards the intercropping system. Further, Analysis of the relationship between level of attitude & profile of farmers revealed that education and mass media exposure were found highly significantly associated with the level of attitude of farmers toward intercropping whereas a significant association was found between age, family type, social expectations, inheritance with level of attitude of farmers toward intercropping system. The paper recommends training of farmers on better utilization of mass media and the training will help farmers in increase in their knowledge level by using mass media and with improved knowledge farmers will have more positive attitude towards intercropping.
Keywords: Attitude; Intercropping; Association; Farmers; Agriculture